2003
DOI: 10.1007/s00701-003-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

Early antithrombotic prophylaxis with low molecular weight heparin in neurosurgery

Abstract: In neurosurgical patients, antithrombotic prophylaxis with certoparin was determined to be safe and efficacious when contraindications are carefully considered and a 12-hour time interval before and after surgery was guaranteed. This retrospective analysis should encourage a prospective trial of early LMWH prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 15 publications
0
52
3
2
Order By: Relevance
“…[16][17][18][19][20][21] Three small randomized trials have also been completed. [22][23][24] In 68 patients with ICH, low-dose heparin starting on day 2 led to a statistically lower rate of PE when compared with 4th or 10th day of initiation.…”
Section: February 2015mentioning
confidence: 99%
“…[16][17][18][19][20][21] Three small randomized trials have also been completed. [22][23][24] In 68 patients with ICH, low-dose heparin starting on day 2 led to a statistically lower rate of PE when compared with 4th or 10th day of initiation.…”
Section: February 2015mentioning
confidence: 99%
“…The majority of cases if they are not related to trauma, surgery or puncture; are due to ruptured renal lesions (such as angiomyolipomas [7][8][9]; however, vascular disorders [10,11] and anticoagulation therapy [12][13][14][15][16][17][18], may also be the underlying cause. Sometimes is not possible to find an abnormality responsible for the bleeding [19] Renal tumours account for 58% to 79% of cases of non-traumatic retroperitoneal haemorrhage [7,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that other risk factors for VTE include age, sex, ethnicity, blood type, length of hospital stay, operative duration, and coagulation status [3,6,[8][9][10]14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Standard prophylactic measures for VTE include chemical anticoagulation, mechanical prophylaxis, and increased ambulation during the post-operative period [36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. This paper seeks to review the relevant and current literature on VTE in brain tumor patients, with particular focus on the risk factors and presenting symptoms of VTE, treatment options for those with VTE, and a review of current prophylactic measures for VTE.…”
Section: Introductionmentioning
confidence: 99%